Publishing of the musical works of Mikalojus Konstantinas Čiurlionis - Kučinskas, Darius (Knygotyra, 2003)
In this article the author surveys the history of over 100 years of publishing M. K. Čiurlionis' music, introduces and evaluates the circumstances that have influenced this process, speculates on the prospective publishing of Lithuanian music. Facilitated by the research of publications of Čiurlionis music, the author reveals specific aspects of publishing of Lithuanian music in general.Music publishing has always involved two issues: expensive preparation of publications (engraving) and skilled professionals (editors, engravers). In the beginning of the Twentieth century it was customary, that the editor was authorized to "correct" the manuscript and to make the work "accessible" for general audience. It is possible, that the distrust in the editorial work was the main reason why Čiurlionis never sought to publish his music. Only a few of his works were published in his lifetime: several short pieces for piano appeared in the "Meloman" magazine, and a collection "Vieversėlis" – arrangements of Lithuanian folk songs.After the death of Čiurlionis, the composer and conductor S. Šimkus was instrumental in promulgation and publishing of Čiurlionis' music. By his initiative seven books of Čiurlionis' compositions were published in Leipzig in 1925. For several decades this was the main reference of Čiurlionis' music.After the death of S. Šimkus in 1943, J. Čiurlionytė continued his work. J. Petronis, who undertook publication of 12 editions, used her editions. Two of them – "Pater noster" and "Autumn" – were published during the World War II. The work was carried on in Soviet time.During the years of Soviet occupation, Čiurlionis was declared "mentally ill". His art was devalued and ignored. His rehabilitation had started only after the death of Stalin. The publication of "Works for piano", edited by J. Čiurlionytė (Vilnius: Vaga, 1957), turned a new page in the scholarship of Čiurlionis' output. This edition, again, was the only reference of Čiurlionis' music in Soviet Lithuania. In 1990 a new collection – "Works for piano" edited by V. Landsbergis (Vilnius: Muzika, 1990) has appeared. In 1957–1975 J. Čiurlionytė has edited and prepared for publication five collections. Unfortunately, "iron curtain" has impeded the promulgation of these publications in the West. Only due to personal relationships several editions have reached authoritative musicians in the West, among them – O. Messiaen.Symphonic poem "The Sea" was published in 1965, on the occasion of composer's 90th birth anniversary. Regrettably, the editor's (composer E. Balsys) approach was too liberal, and the resulting edition contained a number of discrepancies.The symphonic poem "In the Forest" was published in Leningrad in 1975, on the occasion of 100th birth anniversary of Čiurlionis. The editor T. Makačinas has made justice to the manuscript this time, but the polygraph is not exemplary.Two editions were released by foreign publishers: "Album per pianoforte" edited by V. Landsbergis was published in Poland in 1978, and "Ausgewählte Klavierwerke" edited by D. Eberlein was published in Leipzig in 1985. The latter, containing commentaries in English and German, is an example of objective work of a qualified editor. A discography of Čiurlionis' music, provided in the Polish publication, illustrated a progressive and a new approach to music publication.In 1975–1983 "Muzyka" publishing company in Leningrad released several publications edited by V. Landsbergis. Although the editors applied an innovative method of "urtext" in preparing this publication, disrespect to the composer is evident in the work of Soviet editors.For past decade printing of Čiurlionis' music is carried out by Jonas Petronis publishing company in Kaunas. In a period of six years (1996–2000) the company has released all unpublished to date works by the composer, newly edited and published both symphonic poems (full score and parts), complete choral works and works for string quartet. The editorial staff for these publications included notable Lithuanian musicians. The outstanding Lithuanian printing company "Spindulys" did the printing work. Seeking the international recognition, all J. Petronis' publications are released in at least two languages. The publication of facsimile and urtext of Fugue in B flat minor is considered among the most significant releases of the company.J. Petronis publications are gaining popularity in the world. Today they are part of the collections of libraries in England, USA, Germany, France, and Brazil. They can be found in private collections as well.The survey of publishing of Čiurlionis' music provides an insightful information on general setbacks of music publishing world. Lack of professional workers, financial risks, and most importantly – problems of shaping and influencing the governmental policy, to name but a few.Celebrations of birth anniversaries of Čiurlionis have had repeatedly awakened a slumbering Lithuanian society and have had mobilized intellectual and forces for realization of projects long overdue.
Keywords: -